2021
DOI: 10.21831/economia.v17i1.33941
|View full text |Cite
|
Sign up to set email alerts
|

Ease of Doing Business Index: An Analysis of Investors Practical View

Abstract: This study investigates the effect of Ease of Doing Business Index (EDBI) on Return on Investment (ROI). The study employs a cross-sectional survey design covering five years from 2015 to 2019. The sample is 47 registered companies with the Lagos Chamber of Commerce and Industry, which is the most representative of the organised private sector group in Nigeria. The study adopts descriptive and linear regression statistical analysis. Findings show a statistically significant negative effect of Government policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Business growth is made possible by the company's willingness to support the usage of technology. People are more inclined to adopt new technology if they believe doing business is simple (Babatunde et al, 2021). EDB is a crucial marker that reveals the ideal setting for enhancing new technologies and also a key element that influences how willing a population is to adopt innovation.…”
Section: Ease Of Doing Business (Edb)mentioning
confidence: 99%
“…Business growth is made possible by the company's willingness to support the usage of technology. People are more inclined to adopt new technology if they believe doing business is simple (Babatunde et al, 2021). EDB is a crucial marker that reveals the ideal setting for enhancing new technologies and also a key element that influences how willing a population is to adopt innovation.…”
Section: Ease Of Doing Business (Edb)mentioning
confidence: 99%
“…Using a dynamic panel data model from 2004 to 2015, Shabani and Parang (2019) found that the EDB negatively and significantly influenced capital flight in all the studied countries. Another study by Babatunde et al (2021), who utilised the OLS technique, found that the return on investment was significantly negatively impacted by government policy consistency, government procurement procedures, the availability of raw materials and workforce quality. Canare (2018) evaluated the effect of EDB on firms in 120 countries.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…Countries with larger economic freedom score have stronger economy with greater individual GDP. The ease of doing business index shows how favorable the regulatory environment is for business operations (Babatunde, et al, 2021). Global competitiveness index captures micro-economic and macroeconomic foundations of a nation's competitiveness.…”
Section: Literature Review and Asian Emerging Economiesmentioning
confidence: 99%